2016
DOI: 10.14478/ace.2016.1025
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Adsorption and Desorption of Ammonia Using Covalent Organic Framework COF-10

Abstract: Ammonia gas as a hydrogen source has received great attention since the importance of hydrogen gas as a clean energy source increased. However, ammonia is toxic and corrosive to metal such that the absorbent that can store and transport ammonia became an important issue. As an effort to solve this, a large pored covalent organic framework, COF-10 was proposed as an adsorbent for storage and safe transportation of ammonia. During the ammonia adsorption process, boron in COF-10 structure can act as a Lewis acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Moreover, the structural regularity of 2DPs is likely to yield highly homogeneous binding sites with high tunability and selectivity, as opposed to conventional porous polymers. ,,, This structural regularity also enables the investigation and screening of 2DPs by computational methods, which is far more challenging in amorphous polymers systems . As such, many theoretical investigations have suggested that pristine 2DP materials will have high selectivities and capacities, characteristics that support the promise of 2DPs as gas storage and separation materials (refs , , , ,​ , , , , , , , , , , , , , , , , ). Finally, these applications are some of the most experimentally studied because they can be investigated using polycrystalline powders, which is the most commonly isolated 2DP morphology (see section ).…”
Section: Properties and Applications Of Two-dimensional Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the structural regularity of 2DPs is likely to yield highly homogeneous binding sites with high tunability and selectivity, as opposed to conventional porous polymers. ,,, This structural regularity also enables the investigation and screening of 2DPs by computational methods, which is far more challenging in amorphous polymers systems . As such, many theoretical investigations have suggested that pristine 2DP materials will have high selectivities and capacities, characteristics that support the promise of 2DPs as gas storage and separation materials (refs , , , ,​ , , , , , , , , , , , , , , , , ). Finally, these applications are some of the most experimentally studied because they can be investigated using polycrystalline powders, which is the most commonly isolated 2DP morphology (see section ).…”
Section: Properties and Applications Of Two-dimensional Polymersmentioning
confidence: 99%
“…Just as 2DPs can be designed to remove inorganic contaminants from water, they can also be engineered to remove organic molecules from aqueous sources. For example, researchers have shown that 2DPs functionalized with ionic bonding, hydrogen bonding, or hydrophobic motifs can capture ionic dyes, nanoparticles, polymers, or other species of interest from water. ,,,,,,,,,, Typically, these adsorbents are used as microcrystalline powders with high surface areas. The high porosity and small crystallite sizes make these materials efficient platforms for the rapid removal of organic pollutants.…”
Section: Properties and Applications Of Two-dimensional Polymersmentioning
confidence: 99%